Amelioration of Gamma-hexachlorocyclohexane (Lindane) induced renal toxicity by Camellia sinensis in Wistar rats - W. L. N. V. Vara Prasad; Ch. Srilatha; N. Sailaja; N. K. B. Raju; N. Jayasree (Veterinary World, 2016)
Aim: A study to assess the toxic effects of gamma-hexachlorocyclohexane (γ-HCH) (lindane) and ameliorative effects of Camellia sinensis on renal system has been carried out in male Wistar rats. Materials and Methods: Four groups of rats with 18 each were maintained under standard laboratory hygienic conditions and provided feed and water ad libitum. γ-HCH was gavaged at 20 mg/kg b.wt. using olive oil as vehicle to Groups II. C. sinensis at 100 mg/kg b.wt. was administered orally in distilled water to Group IV in addition to γ-HCH 20 mg/kg b.wt. up to 45 days to study ameliorative effects. Groups I and III were treated with distilled water and C. sinensis (100 mg/kg b.wt.), respectively. Six rats from each group were sacrificed at fortnight intervals. Serum was collected for creatinine estimation. The kidney tissues were collected in chilled phosphate buffer saline for antioxidant profile and in also 10% buffered formalin for histopathological studies. Results: γ-HCH treatment significantly increased serum creatinine and significantly reduced the renal antioxidative enzymes catalase, superoxide dismutase, and glutathione peroxidase. Grossly, severe congestion was noticed in the kidneys. Microscopically, kidney revealed glomerular congestion, atrophy, intertubular hemorrhages, degenerative changes in tubular epithelium with vacuolated cytoplasm, desquamation of epithelium and urinary cast formation. A significant reduction in serum creatinine levels, significant improvement in renal antioxidant enzyme activities and near to normal histological appearance of kidneys in Group IV indicated that the green tea ameliorated the effects of γ-HCH, on renal toxicity. Conclusion: This study suggested that C. sinensis extract combined with γ-HCH could enhance antioxidant/detoxification system which consequently reduced the oxidative stress thus potentially reducing γ-HCH toxicity and tissue damage.